2004
DOI: 10.1111/j.2151-6952.2004.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a Behavior Change Model to Document the Impact of Visits to Disney's Animal Kingdom: A Study Investigating Intended Conservation Action

Abstract: Over the last 10 to 15 years, zoos and aquariums have set out to influence visitors' conservation-related knowledge, attitudes, affect, and behavior. In 2000, the Institute for Learning Innovation collaborated with Disney's Animal Kingdom (DAK) on a comprehensive baseline study conducted to assess the outcomes of a DAK experience on visitors in four areas: knowledge, attitudes, affect, and behavior. This article describes one aspect of the comprehensive study: an investigation of the long-term (two-to-three-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 5 publications
5
53
0
Order By: Relevance
“…As such, many zoos strive to effectively convey conservation messages to their visitors [Dierking et al, 2004;Hayward and Rothenberg, 2004;Stoinski et al, 2002]. However, zoo visitors come to an institution with their own needs and expectations.…”
Section: Introductionmentioning
confidence: 98%
“…As such, many zoos strive to effectively convey conservation messages to their visitors [Dierking et al, 2004;Hayward and Rothenberg, 2004;Stoinski et al, 2002]. However, zoo visitors come to an institution with their own needs and expectations.…”
Section: Introductionmentioning
confidence: 98%
“…While others have used slightly different classification systems (e.g. Dierking et al, 2004;Wearing et al, 2006), there is consistency in terms of the constructs captured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies have indeed found that, in the absence of reinforcing experiences after the visit, short-term changes in levels of commitment or planned environmental action do not persist over time (Adelman, Falk & James 2000;Dierking, et al, 2004;Rickinson, 2001). Research in other contexts also suggests that intentions do not automatically convert to sustained, long-term behavioural change (Hwang, Kim & Jeng, 2000;Stern and Oskamp, 1987).…”
Section: Post-visit Learning Reinforcementmentioning
confidence: 99%